Efeito do nitrogênio e silício na produtividade e severidade da mancha de cercospora na cultura do milho - Komatsu, Roberto Akitoshi (2009)
With the aim to analyze the influence of rates of nitrogen and silicon on corn yield (Zea mays L.) in the presence of gray leaf spot (Cercospora zeae-maydis) at Campo Mourão city, were studied experiment randomized blocks with four replicates, design in a factorial scheme with four nitrogen rates in coverage (0, 60, 120 and 180 kg ha-1), four silicon rates sprayed (0; 1,25; 2,50 and 3,75 kg ha-1) and two genotypes corn with different response the gray leaf spot, which were: AG-9010 (low resistance) and DKB-330 (resistance), in a total of 64 plots per genotype. Was observed for both genotypes that the greatest absorption of nitrogen, phosphorus and potassium were related to the decrease of the GLS. The application of silicon rates showed lower onset of disease in the AG 9010 genotype. Nitrogen and silicate fertilization linearly reduced the disease in DKB- 330 genotype. Nitrogen fertilization provides the highest average productivity grain in the 116,1 kg ha-1 (AG-9010) and 120,1 kg ha-1 (DKB-330) rates. Silicon fertilization presented the highest average grain productivity on the 2,31 kg ha-1 rate.